Clinical Practice Guidelines for Early Weaning from Mechanical Ventilation. - Eddy Pereira Valdés (Medisur)
Clinical Practice Guidelines for Early Weaning from Mechanical Ventilation. Weaning is the process, gradual or rapid, that leads to the turn off of mechanical ventilation and allows restoring spontaneous ventilation. The guidelines describe the procedure for rapid weaning from mechanical ventilation and emphasizes on spontaneous ventilation test. It includes assessment guidelines focused on the most important aspects to be accomplished.